MODIFICATION OF BAMBOO GAMES SKIP TO INCREASE JUMPING ABILITY FOR CHILDREN INTELLIGENCES DISORDER WITH MEDIUM LEVEL - Elwa Utari (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: The background of this research is to improve for children intelligences disorder with medium level (x) ability to jump in SLBN 2 Padang. Modification of bamboo skip the game is a game that is fun and requires modifications in the deft jumping. The purpose of this study was to determine whether game modification bamboo can skip jump enhance the ability of the children intelligences disorder with medium level X. This type of research is the design of Single Subject Research AB. The results showed modifications skip the bamboo game can improve jumping ability for children intelligences disorder with medium level X in SLBN 2 Padang.